Interdependent effects of surface and flexoelectricity on the electromechanical behavior of BNRC nanoplate. (December 2022) - Kundalwal, S.I.; Gupta, Madhur
Abstract: The present work deals with the static and dynamic behavior of boron-nitride (BN) reinforced piezoelectric nanocomposite subjected to mechanical load while considering flexoelectric and surface effects. Based on the modified Kirchhoff plate theory and Navier's solution, an analytical model is derived to investigate the electromechanical response of simply supported (SS) boron-nitride reinforced nanocomposite (BNRC) plates. In addition, a micromechanical model by employing the Mori-Tanaka (MT) approach is derived to investigate the effective elastic and piezoelectric properties of the BNRC lamina. The BNRC lamina is composed of BN nanofiber and polyimide matrix, such that the BN nanofibers are oriented along the 3-direction. Our outcomes reveal that the incorporation of the BN nanofiber shows a substantial enhancement in the effective longitudinal and transverse piezo-elastic coefficients of the BNRC lamina. Further, the outcomes of the analytical model by adopting the Kirchhoff plate theory illustrate that the effects of flexoelectricity and surface show significant enhancement in the stiffness of the composite at the nanoscale, although the surface effect is more pronounced when compared with the flexoelectric effect. Based on the present analysis, we observed that the effects of flexoelectricity and surface influence the static and vibrational properties of BNRC. Thus, at the nanoscale, these size-dependent properties cannot be neglected. This work presents an opportunity for the development of high-performance and efficient BNRC nanoplates. Highlights: Analytical model using Kirchhoff's plate theory is developed to study the electromechanical behavior of BNRC plates. Analytical model developed considering surface and flexoelectricity effects, and their combined effect is studied. Micromechanical model is developed to evaluate the effective elastic and piezoelectric properties of BNRC. Static and dynamic responses of simply supported BNRC plates under different loading conditions are investigated. Both flexoelectric and surface effects play crucial role in studting static and dynamic behavior of nanoplates.